The Influence of Leadership Style and Motivation on Employee Work Discipline at PT Duta Setia Pratama Cikarang – Bekasi - Wasilatun Nikmah; Henny Armaniah; Dessy Suryani (Kusuma Negara Business School, 2020)
The population in this study were all employees of the production division of PT. Duta Setia Pratama. The number of samples was determined using the random sampling technique, which then obtained the results of 53 respondents. Data collection tools used were documentation and questionnaires. The research data analysis method uses instrument test (validity test and reliability test), descriptive analysis of classical assumption test percentage, multiple regression analysis, partial test hypothesis testing (t) and simultaneous test (F), and the coefficient of determination. The results of multiple linear regression analysis show the equation Y = 19.075 + 0.208 X1 + 0.336 X2. Partially the magnitude of the influence of each independent variable on the dependent variable, namely: Leadership Style of 17.7%, and Motivation of 12.4%. Simultaneously, the influence of Leadership Style and Motivation on Work Discipline is 43.8%. This study concludes that there is an effect of Leadership Style and Motivation on Work Discipline simultaneously or partially.